MANAJEMEN PENGUATAN SUMBER DAYA KARAKTER RELIGIUS SISWA DI SDS BAYT TAMYIZ SUKAPERNA - Hana Tadzkiya; Nurfuadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of religious character resource management at SDS Bayt Tamyiz Sukaperna. The research focuses on four management functions: planning, organizing, actuating, and controlling within the religious character strengthening program. A qualitative approach with a case study design was employed. Data were collected through observation, in-depth interviews, and documentation involving the principal, teachers, and students. The findings indicate that: (1) planning is grounded in the Al-Qur'an and As-Sunnah, involving all stakeholders; (2) organizing is implemented through role distribution among teachers, coordination with parents, and conditioning of an Islamic school culture; (3) actuating is realized through daily worship habituation, etiquette cultivation, teacher exemplary behavior, and character reinforcement programs such as Galaxy Akhlak and Bintang Akhlak; and (4) supervision is conducted through weekly and monthly evaluations, mutaba'ah-based monitoring, and continuous follow-up. The program has produced a significant positive impact on students' religious character development, reflected in worship consistency, Islamic etiquette, and daily behavior.